KEBUTUHAN KALORI DAN PENENTUAN WAKTU ISTIRAHAT MENGGUNAKAN PENDEKATAN FISIOLOGIS PADA PROSES PRODUKSI DI CV. RIFKY ARAFA - Ramadhan, Muhamad Rafli; Rini, Asih Setyo; Hanan, Siti; Muhammad, Irfan; Ramadhania, Sherin; Setiawan, Lucky (Jurnal Ilmiah Teknik dan Manajemen Industri, 2023)
CV. Rifky Arafa, one of the companies engaged in garments that provides the needs of goods and services for making alma mater, suits, jackets, hats, togas, and bags, located in Kadu Genep Village, Petir District, Serang-Banten Regency. This research was conducted on 5 production operators of sewing machine parts. The purpose of this study was to determine how much calorie needs and how long rest periods needed by operators based on pulse rate and energy consumption and find out the optimal rest time for sewing machine part production process operators. This research method uses a physiological approach method with the calculation of measurement data of 10 pulses, from the calculation of the average working pulse rate (DNK) and cardiovascular load (%CVL) as well as the level of energy consumption needed by the operator when doing work, based on calculations using the highest average physiological approach of the work pulse rate (DNK) with a value of 90, 67 beats/minute and cardiovascular load (%CVL) with an indigo of 18.18% which classified as light workload and can be classified as not fatigue when working because of the value <30% if the %CVL value reaches 30% - 60% then repair or additional hours of rest time are needed. The calorie requirement required by the operator is 0.978 Kcal/min based on the calculation of energy consumption spent during work of 3.606 Kcal/min and energy expenditure at the time before work of 2.628 Kcal/min. For the determination of rest time through the calculation of energy consumption of 0.978 Kcal/min states that no rest time is needed during the work process at the production process operator. (Rt = 0) This means that the rest hours given or that have been set in the CV. Rifky Arafa which is 60 minutes is enough